Telecuidado à pessoa idosa: ações de acolhimento durante a pandemia da COVID-19 - Areosa, Silvia Virginia Coutinho (2022)
The measures to contain the spread of the coronavirus worldwide have required adaptations in daily routine, especially those to risk groups with greater weaknesses in health. Among the strategies to decrease the effects of the spread of the virus is social isolation. However, this strategy can cause emotional complications, in which some of the alternatives available to support health care and quality of life for the population are telecare, telemedicine, and telehealth services. The present experience report aims to present a telecare service for the elderly developed by the university in the first eight months of the pandemic. Telecare worked during weekdays during business hours and assisted 606 people in the municipality of Santa Cruz do Sul/RS. The service sought to understand part of the routine and reality of hundreds of people over 60 years old, without involving any risk to their health.